Al qaeda connection - Williams, Paul L. (New Delhi, 2006)
The author reveals persuasive evidence that al Qaeda has now established connections with the Sicilian Mafia, which is helping to finance terrorism through the sale of heroin. In addition, through its ties to the Chechen Mafia, the group responsible for the heinous attack on a Russian school, al Qaeda has managed to obtain nuclear weapons from poorly secured and carelessly guarded storehouses in Russia.Perhaps the most disturbing evidence uncovered by Williams is the relation of al Qaeda to an obscure Salvadoran street gang, which calls itself Mara Salvatrucha and has expanded exponentially.No other book deals with the connection between international, extremist Islamic terrorism and organized crime-a connection that has made possible the establishment of a well-financed branch of al Qaeda in Latin America and the creation of terrorist cells in major metropolitan areas throughout the United States.
Keywords: Terrorism